2001
DOI: 10.1046/j.1469-0705.2001.00385.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of prenatal diagnosis of congenital heart diseases by ultrasound: experience from 20 European registries

Abstract: Prenatal detection rate of congenital heart disease varies significantly between countries even with the same screening recommendations. The presence of associated malformations significantly increases the prenatal detection rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
256
7
12

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 328 publications
(300 citation statements)
references
References 19 publications
25
256
7
12
Order By: Relevance
“…Unfortunately, most population studies regarding the use of ultrasonography to detect congenital heart disease have reported low sensitivities for abnormalities of the great arteries [10,12,13,28,41,42,63,64]. Studies documenting higher detection rates emphasized routine visualization of the outflow tracts in addition to the usual four-chamber view [8,22,24,25,27,32,36,37,[65][66][67].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, most population studies regarding the use of ultrasonography to detect congenital heart disease have reported low sensitivities for abnormalities of the great arteries [10,12,13,28,41,42,63,64]. Studies documenting higher detection rates emphasized routine visualization of the outflow tracts in addition to the usual four-chamber view [8,22,24,25,27,32,36,37,[65][66][67].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, four of 1000 live births will be affected by severe congenital cardiac malformations, which account for 20% of neonatal deaths and up to 50% of infant deaths attributed to congenital anomalies (2,6). Nevertheless differences exist in the rates of prenatal diagnosis and termination of CHDs across populations, and through time (7)(8)(9), which has an impact on the live birth prevalence of the more severe cases of CHDs, particularly for hypo-plastic left heart syndrome (HLHS) and related morbidity and mortality (3,10). Counseling of parents has become increasingly essential, as the frequency of detecting of fetal abnormalities has increased.…”
Section: Introductionmentioning
confidence: 99%
“…Em avaliação realizada em 20 centros europeus, observou-se que o rastreamento obtido pelo nível I apresenta taxas de detecção que variam entre 8 a 48%, de acordo com o grau de treinamento dos obstetras e ultra-sonografistas na obtenção dos cortes ecocardiográficos básicos 18 .…”
Section: Discussionunclassified